Readings in Chinese literary thought - Owen, Stephen 1946- (Harvard Univ. Press, 1992)
In this dual-language compilation of seven complete major works and many shorter pieces from the Confucian period through the Ch'ing dynasty, Stephen Owen provides fundamental texts in the history of Chinese thought on literature and comments on them extensively. Canonical early statements, prefaces, poems on poetry treatises, short essays, letters, technical manuals - all are represented and placed in their historical and cultural context. Besides discussing individual selections in detail, Owen traces the development of motifs, methods of argumentation, and deep concerns in Chinese literary thought and explains how they diverge from Western literary theory. This beautifully designed volume will be indispensable to students of Chinese literature, while its translations and commentaries will open up Chinese literary thought to theorists and scholars of other languages.
Keywords: Littérature chinoise - Histoire et critique - Théorie, etc; Chinese literature -- History and criticism -- Theory, etc; Geschichte; Quelle; Chinesisch; Literaturtheorie; Chinese literature - History and criticism - Theory, etc